BC reads Adult literacy fundamental English. Course pack. 1 - Ivits, Shantel; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2015)
"This course pack is designed to meet the learning outcomes for Adult Literacy Fundamental English Level 1 (roughly equivalent to beginner to grade 1.5 in the K-12 system). Each of the nine chapters includes a level-appropriate, high-interest reading of approximately 100 words. The readings are freely available in a separate reader with convenient links to the readings in each chapter of this course pack. The online version of this course pack also contains audio recordings of each story in the reader. These recordings, combined with vocabulary and word pattern exercises, prepare the Level 1 student to read each paragraph-long text with greater independence. Font size and line spacing can be adjusted in the online view, and have been enhanced for the print and PDF versions for easier reading. This course pack has been reviewed by subject experts from colleges and universities."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: English language -- Study and teaching -- Foreign speakers -- Textbooks; Electronic books